2008
DOI: 10.2478/v10059-008-0025-4
|View full text |Cite
|
Sign up to set email alerts
|

Personality and Cognitive Performance

Abstract: The two experiments reported here are concerned with the influence of trait anxiety and other individual differences on cognitive performance using the face-in-the-crowd procedure. Participants completed questionnaires (EPQ-R; STAI; Marlowe-Crowne Social Desirability Scale) IntroductionA more recent line of research is concerned with the biasing effects of anxiety on cognitive processes, leading to enhanced awareness of threat (see Eysenck, 2006). It is now commonplace to relate anxiety to the attentional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…Thus, the present study extends, in some important ways, the current literature on the relations between PEN and RTT temperament traits, attentional mechanisms, and stimulation processing. Although there are a few exceptions (e.g., Fajkowska, in press; Fajkowska & Eysenck, 2008), most studies in this area have focused on a single temperament dimension, whereas here the emphasis is on temperament types . Second, the current investigation is likely to contribute to the significant debate on cognitive and cortical mechanisms underlying temperament types within the PEN and RTT approaches.…”
Section: Temperament Attentional Mechanisms and Regulation Stimulationmentioning
confidence: 99%
“…Thus, the present study extends, in some important ways, the current literature on the relations between PEN and RTT temperament traits, attentional mechanisms, and stimulation processing. Although there are a few exceptions (e.g., Fajkowska, in press; Fajkowska & Eysenck, 2008), most studies in this area have focused on a single temperament dimension, whereas here the emphasis is on temperament types . Second, the current investigation is likely to contribute to the significant debate on cognitive and cortical mechanisms underlying temperament types within the PEN and RTT approaches.…”
Section: Temperament Attentional Mechanisms and Regulation Stimulationmentioning
confidence: 99%
“…Much of the research examining individual differences in AC mechanisms have focused on tasks that primarily engage the posterior attentional system (Fajkowska & Eysenck, 2008). However, a range of studies looking at the determinants of individual general adaptation suggests that a crucial contribution to it might be viewed in a balance between posterior and anterior systems of AC (Eysenck et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Corbetta, and Shulman (2002) indicated that anxiety (Neuroticism) impairs efficient functioning of the goal-directed attentional system, and increases the extent to which processing is influenced by the 'bottom-up' attentional system. On the other hand, additional studies (Derryberry & Reed, 2002;Fajkowska & Eysenck, 2008) have shown that highly anxious individuals form a heterogeneous group, which differs in the level of 'top-down' attentional control. Thus, anxious good attenders are able to constrain their automatic tendencies to preferentially process threatening material, as opposed to anxious poor attenders.…”
Section: Main Study: Individual Differences In Detection Of Basic Emomentioning
confidence: 99%